Specification and enforcement of personalized privacy policy for social network - Yuan WANG; Yu-qing SUN; Le-le MA (Tongxin xuebao)
An authorization model was proposed to support personalized privacy preferences in the first-logic privacy preference language.The language allowed users to express personalized privacy preferences.Visitor-role authorization rules based on the attributes of visitors and role-permission assignment rules based on the tags of objects were introduced,which resolve dynamic authorization and fine-grained rights assignment problems.Analyzed privacy policy conflict cases and realized policy consistency verification by Prolog logic programming.Designed a personalized privacy policy management and implementation middleware for social network.In the middleware,it integrated the management of personalized policy into access control system on the existing resources.The experiments show that the policy conflict analysis has good efficiency in the implementation.